Commercial Law Review and Legal Politics Related To The Investment Value Gap of Apple Between Indonesia and Vietnam - Nomensen Freddy Siahaan; Agustina Wati; Ine Ventyrina (Journal of Social Research, 2025)
This  study  employs  normative  legal  research  methods,  which  focus  on  analyzing  legal norms and regulations relevant to the research topic. Normative legal research is a scientific procedure  aimed  at  discovering the truth  through logical  reasoning  based on the  established principles  of  law. This method  relies  on  the  systematic  examination  of  legal  materials, including legislation, case law, and legal doctrines, to provide a comprehensive understanding of  the  issue  under  study.  The  data  used  in  this  study  are primarily  secondary  in  nature, consisting  of  laws,  regulations,  legal  precedents,  and  scholarly  legal  commentaries  that  are pertinent  to  the  topic  of  Commercial Law dan Political Law. Once the relevant legal materials were collected, the data analysis process began with the systematic  interpretation  of  legal  texts,  focusing  on  their  application  to  sexual  violence  and commercial law. This included evaluating the purpose, scope, and application of laws, as well as identifying any inconsistencies or gaps. A comparative legal analysis was also employed, where necessary, to contrast Indonesian laws with international conventions and legal practices from  other  countries,  highlighting  differences  and  suggesting  improvements.  Finally,  the findings were synthesized to propose recommendations for enhancing legal protections against sexual violence and human trafficking. This detailed methodological approach ensures that the research is grounded in thorough legal analysis, enabling readers to understand the steps taken to collect and interpret the data without needing to refer to external sources.